2013
DOI: 10.1016/j.molcel.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Processing-Independent CRISPR RNAs Limit Natural Transformation in Neisseria meningitidis

Abstract: CRISPR interference confers adaptive, sequence-based immunity against viruses and plasmids and is specified by CRISPR RNAs (crRNAs) that are transcribed and processed from spacer-repeat units. Pre-crRNA processing is essential for CRISPR interference in all systems studied thus far. Here, our studies of crRNA biogenesis and CRISPR interference in naturally competent Neisseria spp. reveal a unique crRNA maturation pathway in which crRNAs are transcribed from promoters that are embedded within each repeat, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
278
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(302 citation statements)
references
References 87 publications
16
278
0
5
Order By: Relevance
“…jejuni 81116, Helicobacter mustelae 12198 and Neisseria meningitidis Z2491, consistent with two recent studies (Chylinski et al, 2013;Koonin & Makarova, 2013). While our manuscript was in revision, the first functional study of a type II-C system was reported (Zhang et al, 2013). The type II-C system interfered with natural competence in Neisseria spp.…”
Section: Discussionsupporting
confidence: 88%
“…jejuni 81116, Helicobacter mustelae 12198 and Neisseria meningitidis Z2491, consistent with two recent studies (Chylinski et al, 2013;Koonin & Makarova, 2013). While our manuscript was in revision, the first functional study of a type II-C system was reported (Zhang et al, 2013). The type II-C system interfered with natural competence in Neisseria spp.…”
Section: Discussionsupporting
confidence: 88%
“…coli containing the deltaproteobacteria CasX CRISPR locus was grown to OD 600 =1 at 25°C in SOB media. RNA was extracted by warm phenol extraction, separated on 10% denaturing polyacrylamide gel and blotted as previously described by Zhang et al (2013) 64 .…”
Section: Northern Blotsmentioning
confidence: 99%
“…Additionally, a small RNA referred as tracrRNA (trans-activating CRISPR RNA), which is located upstream of the CRISPR array and complementary to the repeat region of pre-CRISPR RNA plays an important role in crRNA maturation. In addition, it is essential for crRNA mediated DNA recognition and Cas9 mediated targeting in vitro, even for crRNAs that bypass processing (Jinek et al, 2012;Zhang et al, 2013). Cas9 promotes the base pairing between the tracrRNA and the repeat sequence of the pre-crRNA, which then becomes a substrate for double strand specific RNase III (Fig.…”
Section: Type II Crispr Systemmentioning
confidence: 99%
“…However, in case of leaderless CRISPR array as in Neisseria strains (type II-C), the new spacer integration seems to occur et al, 2013). In such CRISPR arrays, transcription may occur from the promoters proximal to CRISPR array (Lillestol et al, 2006; Lillestol et al, 2009;Zhang et al, 2013).The CRISPR-Cas system shows high diversity owing to the dynamic evolution of CRISPR locus, involving numerous rearrangements and horizontal transfer of complete or individual modules and therefore this precludes a simple phylogenetic classification. Recent classification schemes of CRISPR-Cas systems that evolved over the years combine the analysis of signature protein families, features of the architecture of cas loci and the information of the effector modules involved in interference and categorize them into two distinct classes, six types and nineteen subtypes (Haft et al, 2005; Makarova et al, 2006; Makarova et al, 2017a; Makarova et al, 2017b;Shmakov et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation